A REVIEW OF PIG LIVER XENOTRANSPLANTATION: CURRENT PROBLEMS AND RECENT PROGRESS - Zhang, Xuan (Xenotransplantation, 2019)
Pig liver xenotransplantation appears to be more perplexing comparable to heart or kidney transplant, albeit great progress has already been achieved. The relevant molecular mechanisms involving in xenogeneic rejection, coagulopathy, and particularly thrombocytopenia, are extremely messy, and need to be systematically illustrated. Briefly, the deletion of expression of Gal antigens in liver graft highlights the injurious impacts of nonGal antigens that induce severe humoral rejection. The innate immunity, particularly mediated by macrophages and natural killer cells, complexly interplays with inflammation and coagulation disorders. Kupffer cells and liver sinusoidal endothelial cells (LSECs) together mediate leukocyte, erythrocyte, and platelet sequestration, which can be exacerbated by increased cytokine production, cell desialylation, and interspecies incompatibilities. Coagulation cascade is activated by TF release which can be dependent or independent of xenoreactive immune response. Depletion of endothelial anticoagulant and anti-platelet capacity amplify coagulation activation, and interspecies incompatibilities of coagulation-regulatory proteins facilitate dysregulation. LSECs involved in platelet phagocytosis and transcytosis, coupled with hepatocyte-mediated degradation, are responsible for thrombocytopenia. The adaptive immunity could be problematic in future long-term liver graft survival. Currently, relevant evidences and study results of various genetic modifications to the pig donor need to be fully discussed, aiming to identify the ideal transgene combination for pig liver xenotransplantation. In the end, we believe that clinical trials of pig liver xenotransplantation should be initially considered as a bridge to allotransplantation.